Alluvial Sedimentary Records in Indian Precambrian Basins: Implications Toward Unique Precambrian Sedimentary Environment? - Chakraborty, Partha Pratim; Bailwal, Rahul; Paul, Pritam P.; Sharma, Aditi (Frontiers in Earth Science, 2022)
‘Present is the key to the past’ – in this all-inclusive uniformitarianian geological panacea Precambrian continental sedimentation system stands out as an odd candidate. A distinctive nature for Precambrian alluvial sedimentation, not analogous to their Phanerozoic counterparts, is highlighted in literature in absence of rooted vegetation, soil and an overall greenhouse atmospheric condition. Documentation from Precambrian alluvial deposits around the Globe suggests a sedimentation pattern dominated by scree cones, alluvial fans and braid-plains under the combined effects of aggressive weathering and absence of vegetation; ephemeral braid-plains convincingly outweigh the other alluvial systems in the rock record. It is also surmised that Precambrian fluvial systems, unlike their Phanerozoic-modern analogues, maintained unequivocal ephemeral character across different climatic zones with very less chance of assuming meandering channel planform in absence of buffering effects of rooted plant and adequate mud. Local ponding of muddy sediments, though visualized in some rare cases, was mostly connected with generation of local paleoslope and unusual riverine hydrology. Recent studies, however, raised question on actual paucity of mud, documented meander channel planform from Precambrian fluvial records and drawn parallel between character of Pre-Silurian alluvial plain on the surface of Earth and meander channel planforms on the Martian surface, interpreted from satellite imagery data. From collation of data on alluvial deposits from a number of Indian Precambrian basins, augmented by new data from the Bayana basin, a Paleoproterozoic basin in North Delhi fold belt, the present study attempts documentation of nuances and intricacies in Precambrian alluvial sedimentation motif that includes facies architecture and paleohydrology. From an extensive, though not exhaustive, database the study intends to claim establishment of meander channel form in Precambrian river systems at local scale in areas of low discharge and availability of higher silt and mud.